Introducing MOSAIC: a Modular, Open-Source Suite for Assistive Intelligent Control - Braun, Hannah; Sierotowicz, Marek; Egle, Fabio; Scheidl, Marc Anton; Montenegro, Silvana Miranda; Thuerauf, Sabine; Castellini, Claudio (IEEE Access, 2025)
Modern assistive technologies, including prosthetic limbs, orthotic devices, and rehabilitation robots, are increasingly being driven by biosignal-based control systems. However, developing and validating such systems remains challenging owing to the complex signal-processing pipelines, heterogeneous hardware requirements, and limited support for real-time prototyping. We present MOSAIC, an open-source, modular software suite written in C# for real-time biosignal processing and intelligent device control. Configured via human-readable files, MOSAIC enables rapid prototyping through functional units called blocks, which support asynchronous data flow and precise execution timing. The system is hardware-independent and supports a wide range of sensors and output interfaces, including electromyography, inertial sensors, ultrasound, functional electrical stimulation, Internet Protocol over User Datagram Protocol, serial communication, and Bluetooth streaming. A live graphical interface enables interactive experimentation and immediate inspection of system behavior. We demonstrate MOSAIC across real-world applications, including prosthetic limb control, gesture-guided medical systems, and muscle-controlled orthotic devices. Its extensible design supports reproducible experimentation in assistive technologies.
CRIS-Team Scopus Importer:2025-12-26
Keywords: Assistive robotics; biosignal processing; human-machine interaction; machine learning; modular software architecture; open-source software; prosthesis control; real-time systems